Development of smart clothing for military applications using thermochromic colorants. Issue 7 (3rd July 2017) - Karpagam, K. R.; Saranya, K. S.; Gopinathan, J.; Bhattacharyya, Amitava
Abstract: In this study, we have developed color changeable (chameleon-type) printings on cotton fabrics using thermochromic colorants for defense applications. Different colored coatings such as light green, dark green, black, brown, and sandal have been developed using blue and orange thermochromic colorants in combination with turmeric (a natural dye) and graphite. The printed color pattern mimics jungle motif design (classic green and brown camouflage) which transforms to desert color motif on application of heat from external sources (using hot air oven or electrical power). The response time and temperature for each color change and recovery were evaluated in case of direct heating. Further, their performance was also tested by providing heat using different electrical power. The CIE L * a * b * values of the colors were measured using spectrophotometer before and after heating. The printed fabrics' physical properties such as tensile strength, elongation at break, flexural rigidity, and tear strength were also tested before and after printing. The wash property of printed fabrics shows reasonably good fixation of colors to the fabric surface. The chameleon-type camouflage printing described in this work shows promise to use the same fabric for camouflaging at different terrains which essentially reduces the time for shifting troops to different locations.